LGM glaciers in the SE Mediterranean? First evidence from glacial landforms and 36Cl dating on Mount Lebanon. (1st June 2022) - Moulin, A.; Benedetti, L.; Vidal, L.; Hage-Hassan, J.; Elias, A.; Van der Woerd, J.; Schimmelpfennig, I.; Daëron, M.; Tapponnier, P.
Abstract: The hydrological conditions during the Last Glacial Maximum in the Eastern Mediterranean have long been debated. In particular, very little is known about the development of high-altitude glaciers in this region. In the present study, morphological and sedimentological evidence, such as U-shape valleys, glacial cirques, and morainic ridges, are used to identify past glaciers on the western slopes of Mount Lebanon, which is by far the highest topography along the eastern Mediterranean coast (3088 m a.s.l.). The geometry of three paleo-glaciers is reconstructed: one 8-km-long glacial tongue stretching from the highest peak down to an elevation of about 2000 m a.s.l., and two small glacial cirques located at about 2300 m a.s.l. The age of maximum glacier advance is constrained from a 10-m-deep 36 Cl depth-profile within the diamicton of one terminal moraine, and yields an early LGM timing (between 25.4 ± 3.1 ka and 31.2 ± 4.5 ka), which agrees with the chronology of the last maximum glacier extension in the Eastern Mediterranean. The three glaciers together form a consistent group, compatible with an Equilibrium Line Altitude (ELA) at 2400 m estimated using the Accumulation Area Ratio method. A degree-day model is further used to infer the temperature and precipitation conditions required to depress the LGM ELA to 2400 m. Our results suggest that the observed glacier extent is compatible with early LGM paleo-temperature records of the area only under the condition of decreased precipitation relative to modern times. These findings thus support an early LGM climate of the Levant region that was drier than today. Highlights: First evidence of LGM glaciers in the southeastern Mediterranean (Mount Lebanon; 34.25°N) are provided. The geometry of three glaciers is reconstructed and constrains the LGM Equilibrium Line Altitude at about 2400 m a.s.l. Glacial and climate modeling indicates a drier LGM climate than today.